Detection of Emergency Vehicle Using Combination of HSV Color Space and RGB Color Space Technique for Intelligent Traffic Light System - Mohammad Syawaludin Syafiq, Hassan; Mohd Razali, Daud (2013)

(untitled)
One of the factors of traffic congested in a busiest town is due to a traffic light at the road intersection.